A Study on Factors Affecting Adoption of Drip and Fertigation for Horticultural Crops in Dharmapuri District of Tamil Nadu - Indhumathi, K.; Paramaguru, P. (University of Jaffna, 2021)
In Tamil Nadu, drip and fertigation for a horticultural crop was introduced through Tamil Nadu Precision Farming project was implemented by Tamil Nadu Agricultural University, Coimbatore in the Dharmapuri and Krishnagiri districts during 2004-07 as a turnkey project. The yield and income of the farmers increased by three fold, apart from increasing the area under irrigation. A survey was conducted in the Pennagaram block to analyse the factors affecting adoption of drip and fertigation. Fifty farmers were selected from the Pennagarm block farmers’ database of Krishi Vigyan Kendra of Dharmapuri district who had adopted drip irrigation system. Drip adoption index was calculated and based on the drip adoption index the farmers were categorized under three groups. It was found that majority of the farmers fell under the medium category (66%) followed by high adopters (24%) and low adopters (10%). The crop wise and the adoption of fertigation wise grouping was done based on the drip adoption index. It was found that there was significant difference among the drip adoption index crop wise. The correlation effect of the various items under consideration on the drip adoption index showed that the drip adoption index was high among the flower growers. The difference in the interaction effect of the crop and adoption of fertigation showed that this should be critically taken into account that the benefits of fertigation should be further educated to the farmers.
Keywords: drip irrigation; fertigation; drip adoption index; dharmapuri district